2014
DOI: 10.2224/sbp.2014.42.0.s101
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Cheating Behaviors

Abstract: I explored the reasons given by college students for cheating during scholastic examinations. The participants were 26 students from Marmara University in Turkey. It was observed that most of the students identified cheating as taking reminder notes into an examination, getting help during the examination, or theft of knowledge. The tendency to cheat in a variety of ways was found to be high, particularly with regard to the preparation of cheating materials before the examination. While some students justifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The diversity of nomenclatures and taxonomies will not make it easy for educational agents to identify clearly which fraudulent practices they should avoid and which behaviour they should prioritise, incorporating behaviour that respects academic integrity. The analysis of perceptions of academic fraud has therefore received attention from researchers [18,[22][23][24][25][26].…”
Section: Representations and Academic Fraud Practicesmentioning
confidence: 99%
“…The diversity of nomenclatures and taxonomies will not make it easy for educational agents to identify clearly which fraudulent practices they should avoid and which behaviour they should prioritise, incorporating behaviour that respects academic integrity. The analysis of perceptions of academic fraud has therefore received attention from researchers [18,[22][23][24][25][26].…”
Section: Representations and Academic Fraud Practicesmentioning
confidence: 99%
“…Keçeci et al (2011) made use of the ADTS scale with nursing students, finding a 'medium level' of academic dishonesty. There are also a number of studies of staff and student perceptions of cheating in Turkey (Küçüktepe 2014;Yazici et al 2011) and a cross-cultural study using the theory of planned behaviour (Chudzicka-Czupała et al 2016) which suggested that 'subjective norms' may play a greater role in predicting intention to cheat in Turkey (and Poland and the Ukraine) than in Switzerland, USA and New Zealand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We appreciate that it is certainly challenging to mimic a real exam. Although we tried to maintain a challenging exam task and created a reward mechanism to entice cheating (Petisca et al, 2020), it was difficult to recreate the fear of failure and stress caused by a real exam (Küçüktepe, 2014;Fendler and Godbey, 2016). These factors affect a student's propensity to cheat.…”
Section: Discussionmentioning
confidence: 99%